New potential antitumoral di(hetero)arylether derivatives in the thieno[3,2-b]pyridine series : synthesis and fluorescence studies in solution and in nanoliposomes - Queiroz, Maria João R. P. (2012)
New fluorescent methoxylated di(hetero)arylethers in the thieno[3,2-b]pyridine series were prepared by a copper-catalyzed Ullmann-type C-O coupling of the methyl 3-amino-6-bromothieno[3,2-b]pyridine-2-carboxylate with ortho, meta and para-methoxyphenols, using N,N-dimethylglycine as the ligand and Cs2CO3 as the base. The compounds obtained were tested for their inhibitory growth activity in three human tumor cell lines MCF-7 (breast adenocarcinoma), A375-C5 (melanoma), NCI-H460 (non-small cell lung cancer). The di(hetero)arylethers bearing a methoxy group in the ortho and meta positions showed very low GI50 values (1.1 - 2.5 µM) in all the three tumor cell lines. Their fluorescence properties in solution and when encapsulated in different nanoliposome formulations, composed either by egg-yolk phosphatidylcholine (Egg-PC), dipalmitoyl phosphatidylcholine (DPPC), dimyristoyl phosphatidylglycerol (DMPG), dioctadecyldimethylammonium bromide (DODAB), distearoyl phosphatidylcholine (DSPC), with or without cholesterol (Ch), or distearoyl phosphatidylethanolamine-(polyethylene glycol)2000 (DSPE-PEG), were studied. All compounds can be carried in the hydrophobic region of the liposome membrane. The liposomes with incorporated compounds are nanometric in size (diameter lower than 150 nm) and have generally low polydispersity.